The effects of appearance and motion of virtual characters on emotional reactivity. (September 2018) - Mousas, Christos; Anastasiou, Dimitris; Spantidi, Ourania
Abstract: The aim of this study was to examine the influence of appearance and motion of virtual characters on students' emotional reactions. We used four different virtual reality (VR) conditions with different combinations of appearance and motion: that is, a regular-male and zombie-male virtual character each assigned to low- and high-amplitude motion. Participants were asked to wear a head-mounted display (HMD) and observe the virtual content. Immediately after viewing each of the four stimuli, participants were asked questions about their emotional reactions in terms of reactivity (intensity) and subjective valence. Both the appearance and the motion of the virtual characters significantly affected participants' (a) emotional valence in a dynamic pattern and (b) emotional intensity, with reactions to subjectively aversive and/or active stimuli as more negative than reactions to neutral and/or passive stimuli. Females showed significantly higher levels of negative emotional intensity to all virtual characters and negative emotional valence (lower likeability) to aversive characters. Implications for further research, and gender and cultural considerations are discussed. Highlights: Features of virtual characters have a dynamic impact on emotional valence. The appearance and motion of the virtual characters affect emotional intensity. Females show significantly higher levels of negative emotional reactivity. Females have more negative emotional valence to aversive virtual characters. A sense of reality is still strong within virtual world.